2017
DOI: 10.1002/etc.3760
|View full text |Cite
|
Sign up to set email alerts
|

Modeling individual movement decisions of brown hare (Lepus europaeus) as a key concept for realistic spatial behavior and exposure: A population model for landscape-level risk assessment

Abstract: Spatial behavior is of crucial importance for the risk assessment of pesticides and for the assessment of effects of agricultural practice or multiple stressors, because it determines field use, exposition, and recovery. Recently, population models have increasingly been used to understand the mechanisms driving risk and recovery or to conduct landscape-level risk assessments. To include spatial behavior appropriately in population models for use in risk assessments, a new method, "probabilistic walk," was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Topping and Odderskær, 2004; Etterson and Bennett, 2013; Millot et al., 2015; Etterson et al., 2017; Topping and Luttik, 2017; Crocker and Lawrence, 2018; Moore et al., 2018) and mammals (e.g. Wang et al., 2001; Wang and Grimm, 2010; Dalkvist et al., 2013; Liu et al., 2013; Liu et al., 2014; Schmitt et al., 2016; Topping et al., 2016; Kleinmann and Wang, 2017; Wang et al., 2022) demonstrating the potential use of these models in higher tier risk assessments for pesticides.…”
Section: Integrated Exposure and Effect Assessment Tiers For Birds An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Topping and Odderskær, 2004; Etterson and Bennett, 2013; Millot et al., 2015; Etterson et al., 2017; Topping and Luttik, 2017; Crocker and Lawrence, 2018; Moore et al., 2018) and mammals (e.g. Wang et al., 2001; Wang and Grimm, 2010; Dalkvist et al., 2013; Liu et al., 2013; Liu et al., 2014; Schmitt et al., 2016; Topping et al., 2016; Kleinmann and Wang, 2017; Wang et al., 2022) demonstrating the potential use of these models in higher tier risk assessments for pesticides.…”
Section: Integrated Exposure and Effect Assessment Tiers For Birds An...mentioning
confidence: 99%
“…Prosser, 2010;Ludwigs et al, 2017;Ludwigs et al, 2022), while species-specific PT values also may show considerable variation between crops, agricultural landscapes and seasons (e.g. Prosser, 2010;Kleinmann and Wang, 2017).…”
Section: Tracking and Pt Estimationmentioning
confidence: 99%
“…The démographie framework also led some studies to emphasize the possibility of compensation between PPP-induced mortality or reduced fecundity and the release of natural density-dependent Controls (e.g., compétition) that buffer PPP population impacts (Stark and Banks, 2003;Stark, 2012). These processes hâve been investigated in wild rodents (Wang et al, 2001;Wang and Grimm, 2010), in relation to territorial behavior in hsh (Mintram et al, 2018) or hare (Kleinmann and Wang, 2017), in soil invertebrates (Reed et al, 2016), in pollinators (Bryden et al, 2013), and in plants . This effect of density level led some authors to point out the specihcity of the démographie response of rare or endangered species to PPP exposure (Topping et al, 2005).…”
Section: A Ssessm Ent Of the Relevance Of P P P Effects Observed On I...mentioning
confidence: 99%
“…The modelling software POLARIS has been chosen as it is frequently used for population modelling for the risk assessment of pesticides. The models are spatially explicit individual based models, which have been parameterised based on public literature (see [27,61,62]), models are summarised in the Additional file 1). Monte Carlo simulation is used to capture the variability of model parameters.…”
Section: Simulations With Population Modelsmentioning
confidence: 99%
“…Topping and Odderskaer [57] demonstrated that changing the landscape structure had a stronger impact than pesticide application for the skylarks (Alauda arvensis) population. Kleinmann and Wang [27] compared field use predicted by a population model for brown hare (Lepus europaeus) with empirical data in several landscapes in the UK. They found that landscape structure had a strong impact on field use.…”
Section: Introductionmentioning
confidence: 99%